History of nordic computing 4 : 4th IFIP WG 9.7 Conference, HiNC 4, Copenhagen, Denmark, August 13-15, 2014, Revised selected papers /: 4th IFIP WG 9.7 Conference, HiNC 4, Copenhagen, Denmark, August 13-15, 2014, Revised selected papers. (2015) - Unknown
No abstract available